(untitled) (Advances in Applied Mathematics and Mechanics, 2019)
This paper is concerned with the C^0 weak Galerkin finite element method for a fourth order linear parabolic equation. The method is based on the construction of a discrete weak Laplacian operator. The error estimates are obtained for semi-discrete weak Galerkin finite element method. Numerical results are presented to confirm the theory.